Visualization of Autophagy Progression by a Red-Green-Blue Autophagy Sensor - Kim, Heejung; Kim, Hyunbin; Choi, Jaesik; Inn, Kyung-Soo; Seong, Jihye (AMER CHEMICAL SOC, 2020)
Autophagy is a major degradation process of cytosolic components and misfolded proteins that is crucial for cellular homeostasis and for the pathogenesis of diverse diseases. Autophagy is initiated by the formation of phagophores, which mature to autophagosomes. The autophagosomes then fuse to lysosomes to form autolysosomes. Different stages of autophagy can be deregulated to cause autophagy-related diseases, and thus, an accurate detection of each stage of autophagy progression is critical for efficient therapeutic strategies for these diseases. To identify the different stages of autophagy progression, here, we developed a new autophagy flux sensor, named red-green-blue-LC3 (RGB-LC3). RGB-LC3 is composed of LC3 and red-green-blue (RGB) fluorescent proteins, which were carefully chosen by considering their separate spectral profiles, stability, brightness, and most importantly different pH sensitivities. Utilizing this RGB-LC3 and the predicted pH, we could clearly identify phagophores, autophagosomes, fusion stage, early autolysosomes, and mature autolysosomes in live cells. Furthermore, the RGB-LC3 sensor was successfully applied to distinguish different effects of A beta monomers and oligomers on autophagy flux. Therefore, we developed a new autophagy flux sensor, RGB-LC3, which may be a valuable tool to further investigate the molecular mechanisms of autophagy and to develop efficient therapeutic strategies for autophagy-related diseases.
Keywords: PROTEIN; LC3; DEGRADATION; COMPLEX; FLUX; MACROAUTOPHAGY; PATHOGENESIS; MONOMERS; ASSAYS; BACE1